Enter production sharing contract for oil (P.S.C) - خلف فاروق عز الدين; المخزومي وليد مرزة (Journal of Legal Sciences, 2021)
This research discusses the procedural aspect of oil contracts, as one of them is the sharing in production contract which has the same importance comparing with other aspects, as the legislator, in oil countries, is requiring the availability of certain procedures to enter such oil contracts, related with high importance issues such as the followed procedures by the competent administration in that oil country to choose the company they deal with, also the required procedures to be done to enter negotiations with those companies for maintaining equal mutual interests for both parties. One of those needed procedures is to sign the contract by the competent entity stated by law, also the necessity to present such contract to the Legislature or any other qualified body for reviewing and confirming.